2020
DOI: 10.1111/apt.15720
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: the most commonly used IBD indices still fail to represent real life and subjective patient experience

Abstract: LINKED CONTENT This article is linked to Lauriot dit Prevost et al and Pariente papers. To view these articles, visit https://doi.org/10.1111/apt.15681 and https://doi.org/10.1111/apt.15736.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The study relied on subjective, rather than objective, measures of symptomology. Patient reports are becoming important outcome measures for clinical research ( 64 ), however, some studies have found subjective measures of patient functioning do not always correlate with objective measures of disease activity ( 65 , 66 ). Future studies exploring the relationship between endoscopy or biomarkers and SWB would provide a fuller picture.…”
Section: Discussionmentioning
confidence: 99%
“…The study relied on subjective, rather than objective, measures of symptomology. Patient reports are becoming important outcome measures for clinical research ( 64 ), however, some studies have found subjective measures of patient functioning do not always correlate with objective measures of disease activity ( 65 , 66 ). Future studies exploring the relationship between endoscopy or biomarkers and SWB would provide a fuller picture.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare providers play an important role in educating patients and enabling them to participate actively in their treatment through shared decision‐making. Such participatory models that integrate quantity and quality using, for example, quality‐adjusted life years and subjective patient scores as metrics of therapeutic effectiveness, minimise the risk of unnecessary costs arising from solely objective, ineffective or poorly managed treatments 8 …”
mentioning
confidence: 99%
“…Such participatory models that integrate quantity and quality using, for example, quality-adjusted life years and subjective patient scores as metrics of therapeutic effectiveness, minimise the risk of unnecessary costs arising from solely objective, ineffective or poorly managed treatments. 8 The transformation of IBD healthcare costs, as elegantly documented and illustrated by the Swedish experience, calls for a reassessment of priorities and judicious decisions on the use of, and indications for, innovative therapies to ensure more equal access to IBD healthcare in the next decades. The pursuit of a sustainable path forward demands embrace of qualitative and quantitative value-based healthcare principles to support decisions on treatment strategies.…”
mentioning
confidence: 99%
“…I would like to thank Drs Creemers, Bloem and Bodegraven for their editorial which underlined the importance of objective and subjective parameters for the evaluation of Crohn's disease (CD) patients 1 . Indeed, the tools used in CD at present (clinical, biological and endoscopic) only assess inflammatory activity and cannot evaluate the progressive characteristics or the patient's subjective perception of the disease.…”
mentioning
confidence: 99%